2013
DOI: 10.1039/c2dt32161k
|View full text |Cite
|
Sign up to set email alerts
|

ZIF-8 crystal coatings on a polyimide substrate and their catalytic behaviours for the Knoevenagel reaction

Abstract: ZIF-8 crystal coatings were prepared by direct growth on different flexible polyimide substrates including a thin membrane and electrospun nanofiber mat. In SEM pictures, the ZIF-8 crystals exhibit a rhombic dodecahedron morphology. Owing to the flexible polyimide substrate, the MOF-polymer film may be moderately bent or easily tailored when not destroyed. The ZIF-8 coatings can be activated at high temperature owing to the excellent thermal resistance and low coefficient of thermal expansion of the polyimide.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 35 publications
1
53
0
Order By: Relevance
“…For a practical use, deposition of MOFs on substrates to fabricate MOFs thin films have attracted much attraction due to their potential applications in catalysis, sensors, and gas separations [8][9][10].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…For a practical use, deposition of MOFs on substrates to fabricate MOFs thin films have attracted much attraction due to their potential applications in catalysis, sensors, and gas separations [8][9][10].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…MOFs have drawn considerable attention in recent years owing to fine tune size, shape, and chemical functionality of the cavities and the internal surfaces by changing the organic liker groups [1][2][3].With such exceptional properties, MOFs have great potential in diverse applications such as catalysis, drug delivery, gas _________________________________ ACCEPTED MANUSCRIPT 2 adsorption, magnetic imaging and sensing [4][5][6][7]. For a practical use, deposition of MOFs on substrates to fabricate MOFs thin films have attracted much attraction due to their potential applications in catalysis, sensors, and gas separations [8][9][10].Recently, several synthesis schemes have been developed for the fabrication of MOFs thin film on different solid substrates, such as silica, porous alumina, graphite and gold surfaces [11][12]. Diverse synthesis approaches for MOFs thin films and membranes have been employed, and can be classified into two approaches: One is in situ or by secondary growth after seeding from a supporting membrane, and the other is to incorporate pre-synthesized MOFs into matrix materials to form mixed-matrix membranes (MMMs) [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12-14 Three-dimensional PCPbased architectures possessing a multimodal porosity are useful to improve the molecular diffusion when used as separation systems and catalysts. 15,16 Owing to the highly reactive surfaces of PCPs (composed of partially coordinated organic ligands or uncoordinated metal centers), the possible modulation of the coordination equilibrium, and the large number of PCP framework available (implying a large range of possible synthesis conditions), many of the chemical and microfabrication methods established for the manipulation of both purely organic and inorganic compounds were applied for the synthesis of PCPs. As it will be illustrated later in this chapter, utilization of microwave treatment, microemulsion methods, or capping agents was successful for the control of the size and shape of PCP crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The second strategy is the in situ growth of MOFs on the electrospun nanobers. 8,[41][42][43][44][45][46][47][48][49][50][51][52][53] Peterson and Parsons found that Zr-based MOF thin lms could be formed in situ on the TiO 2 coatings, which was deposited via atomic layer deposition onto polyamide-6 electrospun nanobers. 51 Another work presented by Ma and coworkers showed that bimetal ZIFs could directly grow on 2-methylimidazole/PAN electrospun nanober mats, which showed excellent electrocatalytic performance for oxygen reduction reaction aer the carbonization step.…”
Section: -40mentioning
confidence: 99%